2018
DOI: 10.1038/s41598-018-27316-1
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of social and economic and pregnancy exposures with blood pressure in UK White British and Pakistani children age 4/5

Abstract: South Asians have higher rates of coronary heart disease (CHD) than White European individuals. Blood pressure (BP) is one of the most important risk factors for CHD and ethnic differences in BP have been identified in childhood. Early life exposures could explain some of these differences. We examined associations of family social and economic and maternal pregnancy exposures and BP at age 4/5 in 1644 White British and 1824 Pakistani mother-offspring pairs from the Born in Bradford study. We found that systol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 43 publications
4
11
0
Order By: Relevance
“…By age 4-5 years, the positive effect of maternal gestational hyperglycaemia seems to have attenuated, though greater maternal early pregnancy adiposity remains associated with greater offspring adiposity at this age [5]. We have also shown that Pakistani women are less likely to experience hypertensive disorders of pregnancy (HDP) compared to white British women, but that HDP is more robustly associated with offspring BP at age 4-5 years in Pakistani compared to white British children [4].…”
Section: Priority Research Areasmentioning
confidence: 78%
See 4 more Smart Citations
“…By age 4-5 years, the positive effect of maternal gestational hyperglycaemia seems to have attenuated, though greater maternal early pregnancy adiposity remains associated with greater offspring adiposity at this age [5]. We have also shown that Pakistani women are less likely to experience hypertensive disorders of pregnancy (HDP) compared to white British women, but that HDP is more robustly associated with offspring BP at age 4-5 years in Pakistani compared to white British children [4].…”
Section: Priority Research Areasmentioning
confidence: 78%
“…Follow-up since then has included growth and blood pressure measures by primary school nurses at age 5-6, [4,5] whole cohort record-linkage to health and educational data, e.g. [6,7], detailed bespoke data collection with sub-samples [8][9][10], and addition of biomarker data using stored biological samples, including genome-wide data, metabolomic data and Deoxyribonucleic acid (DNA) methylation [11,12].…”
Section: The Existing Bib Resourcementioning
confidence: 99%
See 3 more Smart Citations